PENGEMBANGAN PERANGKAT PEMBELAJARAN BAHASA INDONESIA (CERPEN) MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TORNAMENTS (TGT) PADA SISWA KELAS X SMA NEGERI 11 MAKASSAR - Andi Karman (Universitas Negeri Makassar, 2016)
Abstract: Software Development Learning Indonesian (Short Story) Model Cooperative Learning Teams Games Tornaments (TGT) in Class X SMAN 11 Makassar. This research aims to develop learning tools with cooperative learning model type Teams Games Tournaments (TGT) in class X SMA Negeri 11 Makassar and expected an increase learning achievement of learners. Design test product designs in development using quantitative research, namely quantitative descriptive. This research was conducted in SMA Negeri 11 Makassar. The trial results is known that the learning device TGT learning model is effective and practical, the test results showed that the average score obtained by the students on achievement test is 87.68 of the ideal score of 100 with a standard deviation of 4.91. Number 39 of 41 students or 92.6% meet the individual mastery. These data show that the classical completeness is reached. In general, the students responded positively to the learning device that digunakan.Tingkat teacher's ability to manage the process of cooperative learning teams tournamens games (TGT) are included in the category of very high, meaning that the teacher performance can be maintained.